(x+4)(x+6)=0
x = -4, x=-6
The answer is C.
The answer is C 28 I hope this helped :)
9514 1404 393
Answer:
- to interest: $532.97
- to principal: $54.23
- new balance: $79,891.90
Step-by-step explanation:
The interest is found by multiplying the monthly rate by the balance on the loan. For the first month, the balance is the loan amount.
$79,946.13 × 0.08 ×(1/12) . . . . . one month = 1/12 year
= $532.97
The interest amount in the first payment is $532.97.
__
The amount of the first payment that goes to principal is what is left after the interest is paid:
$587.20 -532.97 = $54.23 . . . amount to principal
__
The new balance is the previous balance less the amount to principal:
$79,946.13 -54.23 = $79,891.90 . . . new balance
3√1024<span>= 10.079368399159
That's your answer.
</span>
I'm assuming the given log equation is ![\log_{\text{x}}(49) = \text{x}](https://tex.z-dn.net/?f=%5Clog_%7B%5Ctext%7Bx%7D%7D%2849%29%20%3D%20%5Ctext%7Bx%7D)
If so, then the exponential form is ![\text{x}^{\text{x}} = 49](https://tex.z-dn.net/?f=%5Ctext%7Bx%7D%5E%7B%5Ctext%7Bx%7D%7D%20%3D%2049)
This is because the general form
transforms into ![\text{y} = \text{b}^{\text{x}}](https://tex.z-dn.net/?f=%5Ctext%7By%7D%20%3D%20%5Ctext%7Bb%7D%5E%7B%5Ctext%7Bx%7D%7D)
For both equations, the 'b' is the base.